Identification of Pathogenic Bacteria in Food Samples from Cafeterias of a University in Denpasar, Indonesia - , Anak Agung Ayu Lila Paramasatiari; , Putu Indah Budiapsari; Suryanditha, Putu Arya; Widhidewi, Ni Wayan (Folia Medica Indonesiana, 2022)
Highlights: • Eschericia colli was the most contaminant bacteria among food samples from Warmadewa Cafeterias • Further suggestions to increase the hygiene in food processing must be offered. Abstract : Foodborne diseases still remain a problem especially in public areas. This study aimed to identify pathogenic bacteria in foods sold at the cafeterias of Universitas Warmadewa, Denpasar, Indonesia. The presence of pathogenic bacteria in the food samples was identified using the brain heart infusion (BHI) agar for the growth of Escherichia coli and Streptococcus aureus, selenite for Shigella and Salmonella, and alkaline peptone for Vibrio cholerae, then bacterial culture was conducted to identify the species. The results showed that Escherichia coli were found in two food samples, kangkong and jinggo rice, with the colony counts of 50-118. Escherichia coli was the most commonly found contaminant in food samples from the Warmadewa Cafeterias. Further suggestions must be offered to increase hygiene in the food processing by advising the stalls' owners to serve good foods and conducting regular inspections to assess the food quality.